Fermentation and Anaerobic Oxidation of Organic Carbon in the Oxygen Minimum Zone of the Upwelling Ecosystem Off Concepción, in Central Chile - Srain, Benjamín M.; Sobarzo, Marcus; Daneri, Giovanni; González, Humberto E.; Testa, Giovanni; Farías, Laura; Schwarz, Alex; Pérez, Norma; Pantoja-Gutiérrez, Silvio (Frontiers in Marine Science, 2020)
We studied the dynamics of fermentation and anaerobic degradation of organic matter at a fixed station in the Oxygen Minimum Zone (OMZ) within the Humboldt Current System off Concepción, central Chile. Products of the main anaerobic microbial reactions [fermentation, denitrification, and reduction of Fe(OH)3 and SO42–] were analyzed during laboratory incubations of OMZ waters. Fermentation of glucose and amino acids resulted in the production of volatile fatty acids, mainly acetate; these compounds were detected year-round in in situ water samples and were associated with high primary production rates and presence of O2-deficient waters at the sampling site. In contrast, whilst ethanol was produced from glucose fermentation by OMZ water microorganisms under laboratory conditions, it was not detected in the water column during the annual cycle. Evidence of acetate oxidation (which is thermodynamically feasible), with Fe(OH)3 as an electron acceptor, suggests that microbial activity could reduce solid-phase Fe carried by rivers using fermented metabolites in oxygen-depleted water, thus releasing dissolved bioavailable Fe. Here we present evidence for productivity-driven seasonality of biogeochemical cycles in the Humboldt system, supported by fermentation and anaerobic consumption of fermentation products oxidized by a variety of electron acceptors including NO3–, Fe(OH)3, and SO42–. Our results suggest that products of fermentation in the OMZ may provide a source of labile organics for advection to oxygenated waters of subantarctic origin during austral winter. Fermentation, anaerobic oxidation and associated advection of fermentation products are likely to be enhanced during the twenty-first century due both to temperature increase and decrease in dissolved O2 in the water column.